math

posted by .

24= -2(b-3)+8


I suppose you want to solve
24= -2(b-3)+8
for b, am I right?
If so, subtract 8 from both sides to get
16 = -2(b-3)
divide both sides by -2 to get
-8 = b-3
then add 3 to both sides to get
-5 = b
then check the answer
24 = -2(-5-3) + 8 = 16 + 8

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how do you solve 9x=6 9x=6 Divide both side by 9. (Remember you can add, subtract, multiply, etc but do to both sides what you do to one.) 9x/9 = 6/9 The 9's divide out on the left leaving x. x = 6/9. I will let you reduce the answer. …
  2. math

    can anyone help me with these 3 problems I am trying to check my daughters hoime work it has bee na few years. 1. The sum of n and twenty -two, multiplied by three, is 78 2. the product of z and 17 is less than or equal to the difference …
  3. Math

    How would I would I solve this problem -25-75h=h+25 Add 25 to both sides. Subtract h from both sides. This should leave you with -76h = 50 Finally, divide both sides by -76
  4. algebra

    I need a step by step explanation on how to add these two equations 2x+3y=1 5x+3y=16 Subtract the first equation from the second. (Subtract left and right sides separately). This gives you 3x = 15 Then divide both sides by 3. x = 5 …
  5. math

    Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T 8a+2=6b In the first example, divide both sides of the equation by 2 In the second example, add n to both sides of the equation. Try these yourself. They aren't …
  6. math

    I need help figuring out these two questions on euations with integers. -5x+20=-60 2x-3=-2 thank you so much for first: subtract 20 from both sides, simplify, then divide both sides by -5 for second: add 3 to both sides, simplify, …
  7. help please

    What is the first step in solving the problem, 3x-8/12=9?
  8. Math

    Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + 35 What operation solves the equation for m?
  9. ALgebra

    Indicate and explain the logical error in the following set of algebraic expressions Let a=b square both sides to get a^2=b^2 a^2=b*b Since a=b, then a^2=a*b Subtract b^2 from both sides a^2-b^2=a*b-b^2 Factor both sides: (a+b)(a-b)=b(a-b) …
  10. Algebra

    Which of the following describes a correct method for solving the equation below?

More Similar Questions